Effect of aspirin treatment on abacavir-associated platelet hyperreactivity in HIV-infected patients. (15th July 2018) - Falcinelli, Emanuela; Francisci, Daniela; Schiaroli, Elisabetta; Minuz, Pietro; Orsini, Sara; Malincarne, Lisa; Sebastiano, Manuela; Mezzasoma, Anna Maria; Pasticci, Maria Bruna; Guglielmini, Giuseppe; Baldelli, Franco; Gresele, Paolo
Abstract: Background: Ischemic cardiovascular events are a relevant cause of morbidity and mortality in HIV-infected patients. Use of abacavir (ABC), a nucleoside analog reverse transcriptase inhibitor, has been associated with increased risk of myocardial infarction (MI) and with platelet hyperreactivity. We explored whether low-dose aspirin reduces in vivo platelet activation and platelet hyperreactivity induced by ABC in HIV-infected subjects. Methods and results: In a randomized, placebo-controlled, cross-over study forty HIV-infected patients with ABC-associated platelet hyperreactivity, defined by a score based on laboratory variables reflecting in vivo platelet activation and ex vivo platelet hyperresponsiveness, were randomized to aspirin 100 mg daily for 15 days with subsequent cross-over to placebo for additional 15 days or placebo for 15 days with subsequent cross-over to aspirin for further 15 days. In vivo and ex vivo platelet activation markers were measured at day 15 and 30. One group of healthy subjects, one of untreated HIV infected-patients and one treated without ABC, were studied concomitantly. Serum TxB2 and urinary 11-dehydro-TxB2 were decreased by aspirin in ABC-treated patients, but not as much as in healthy controls. Aspirin therapy reduced significantly platelet hyperreactivity (score: from 9.3, 95% CIs 8.7 to 10.0, to 7.5, 6.9 to 8.0), however without bringing it back to the levels of healthy controls (score: 4.6, 95% CIs 3.6 to 5.6). Conclusion: Aspirin reduces ABC-induced in vivo platelet activation and platelet hyperreactivity in HIV-infected patients, however without normalizing them. Whether the observed reduction of platelet activation is sufficient to prevent cardiovascular events requires a prospective trial. Highlights: Treatment of HIV-patients with abacavir (ABC) induces platelet hyperreactivity. Treatment with low-dose aspirin blunts ABC-platelet reactivity. The degree of inhibition was apparently lower than the inhibition usually observed in healthy subjects.